The Single Session Courts Analytical study In light of the UAE Federal Civil Procedures Law and its Regulations - AL Kattan, Mhd Samer Taoufiq (Dirasat: Shari’a and Law Sciences, 2022)
Objectives: This research aims to study the provisions of the single session courts, figuratively called the "one-day court", which was recently introduced by the UAE legislator to contribute to solving the problem of slowness in litigation procedures. Methods: The research adopted the descriptive and analytical approach by analyzing the legal nature of the single session chambers by reviewing the cases submitted to them. Results: The research reached for the following results: before submitting the case to the single-session courts, it must be prepared by the case management office, and that it is adjudicated by the competent court in only one session, and that the reasons for the dispute are placed in the case file at the same session, and the verdict is subject to appeal by way of appeal, and that the appeal verdict is in turn subject to appeal by way of cassation if its conditions are met. Conclusions: Provide for the creation of another type of First Instance Courts and call it "single-session courts" in addition to partial courts and full courts, instead of single-session chambers, and to reduce the time of appeal of judgments issued by them to the extent that is incompatible with the purpose of their creation.